Selection response for Streptococcus agalactiae resistance in Nile tilapia Oreochromis niloticus - Wasana Suebsong; Supawadee Poompuang; Prapansak Srisapoome; Skorn Koonawootrittriron; Amorn Luengnaruemitchai; Harry Johansen; Morten Rye (Journal of Fish Diseases, 2019)
The potential of selection to improve resistance to streptococcosis was evaluated in a commercial population of Nile tilapia in Thailand. The base generation (G0) consisted of offspring from 98 sires and 149 dams using a partly nested design. At 60 days post‐hatch, 30 fish from each family were injected intraperitoneally with a Streptococcosis agalactiae solution (1 × 10 9 CFU/ml) and evaluated for 14 days. Disease resistance was recorded as the number of days from challenge until death (DD) and as a binary (BIN) trait (dead/alive) on day 14. Three models were used for genetic analyses: Cox frailty model for DD; animal model for DD; and animal model for BIN. Age at challenge was fitted as a covariate and contemporary group as fixed or random effect, depending on the model. Fish from the 18 most resistant families were selected to produce the first generation (G1). Heritability estimates for G0 were 0.22, 0.14 ± 0.02 and 0.11 ± 0.02 for the Cox, linear DD and linear BIN models, respectively. Selection response indicated that the risk of death decreased to 54%, survival time increased to 3.4 days and survival rate increased to 21%. These results suggest that genetic improvement is possible for this population.